Enhancing pre-service teachers’ TPACK through the integrating of community of practice and lesson study - Cojorn, Kanyarat; Seesom, Chaweewan (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study explores the impact of a combined community of practice (CoP) and lesson study (LS) approach on fostering technology pedagogical content knowledge (TPACK) in student teachers. TPACK encompasses various knowledge areas, including technological knowledge (TK), content knowledge (CK), pedagogical knowledge (PK), pedagogical content knowledge (PCK), technology content knowledge (TCK), and technology pedagogical knowledge (TPK). The study employs combined CoP-LS practices in two distinct CoPs: CoP A characterized by varied experiences, and CoP B comprising members with comparable experiences. Data gathered through questionnaires and group discussions. The findings reveal that the CoP-LS activities effectively enhance TPACK among student teachers, leading to improved confidence in designing learning activities. Both CoP A and CoP B show overall enhancements in TPACK, with CoP A exhibiting superior development across all dimensions. Further analysis demonstrates that CoP A exhibits greater advancements in PK and PCK, transitioning from the adapting level to the advancing level. Moreover, TCK and TPK demonstrate progress from the exploring level to the advancing level within CoP A. In contrast, CoP B showcases advancements in TK from the exploring level to the advancing level, while no notable changes are observed in CK, PK, PCK, TCK, and TPK.